ENHANCING AUDIT QUALITY IN ENERGY COMPANIES: THE ROLE OF AUDIT FIRM ROTATION ALONGSIDE AUDIT COMMITTEE GENDER DIVERSITY AND CEO DUALITY - Marsha Tiodora Pitaloka; Ricky Ricky (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study examines the influence of gender composition in audit committees, public accounting firm rotation, and CEO duality on audit quality in energy companies listed on the Indonesia Stock Exchange. Audit quality is a crucial aspect in maintaining transparency and integrity in financial reporting, serving as a primary tool for decision-making and oversight in the capital market. Using logistic regression on 55 company samples, the study’s findings indicate that KAP rotation, gender diversity in audit committees, and CEO duality (serving as both CEO and chairman of the board of commissioners) have a positive and significant impact on improving audit quality. The coefficients and odds ratio values indicate that the presence of female members in the audit committee increases the likelihood of audit quality by 5.5 times, while auditor rotation and CEO duality each increase the likelihood by approximately 2 and 4.7 times, respectively. These findings strongly support agency theory and information asymmetry theory, which emphasize the importance of governance structures in ensuring quality audits to mitigate the risk of financial statement fraud.